Regarding confirming technical specifications of doors - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the confirmation on technical specifications including size, color, pattern, material of doors for BRACU new campus project.